(untitled) (Scientific journal of the Fergana State University, 2023)
The presence of cation exchange sulfogroup and anion exchange aminogroups in the polycomplexon obtained on the basis of amination of sulfocationite is confirmed by IR spectroscopy. The kinetics of sorption of cobalt (II) and chromium (III) ions from aqueous solutions was studied under static conditions, and Langmuir constants were found at various temperatures. Based on the studies, the thermodynamic parameters of the sorption process were found: changes in the values of the isothermal - isobaric potential (ΔG), enthalpy (ΔН) and entropy (ΔS).